From the Editor: Starting the Next 30 Years. (1st March 2022) - Kelly, Rob
Abstract : As noted in the Winter 2021 issue of Interface, we have now wrapped up three decades of bringing ECS members and the outside world insights into the wonderful world of electrochemical and solid state science. To calibrate, thirty years ago I had a full head of hair. More or less (less). In going through the archives—a reminder that ALL issues are available in pdf in our archive—one can follow the major changes that have taken place in scientific publishing.